The Influence of Social Comparison, Materialism, and Negative Affect on Impulsive Buying with Confidence as A Moderating Variable Among E-Commerce Consumers in Jakarta - Levi Jehian; Sihombing, Sabrina O. (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Impulsive buying behaviour has become a crucial topic in consumer research in the era of e-commerce growth in Jakarta and the rise of paylater services in Indonesia. This study aims to analyse the influence of social comparison, materialism, and negative affect on impulsive buying, with confidence as a moderating variable. Data were collected through an electronic questionnaire from 230 respondents aged 18–30. After conducting reliability and validity tests, hypothesis testing was performed using PLS-SEM. The results show that five out of seven hypotheses are supported. Social comparison has a significant positive impact on materialism and negative affect but does not significantly affect impulsive buying. Furthermore, materialism was found to increase both negative affect and impulsive buying behaviour. The findings also indicate that negative affect does not have a significant impact on impulsive buying. Confidence successfully moderates the relationship between social comparison and both materialism and impulsive buying, suggesting that individuals with higher levels of confidence are more capable of resisting impulsive urges and are less influenced by social pressure. This study provides important insights for businesses to design more ethical and effective marketing strategies while helping consumers make wiser financial decisions.